Popping pills in youth elite sports—Fact or fiction? A 36-week prospective cohort study of analgesic use in 1,195 youth elite athletes and student controls - Pedersen, J. R.; Møller, M.; Kamuk Storm, L.; Koes, B.; Mohammadnejad, A.; Thorlund, J. B. (Journal of Orthopaedic & Sports Physical Therapy, 2024)
OBJECTIVE To investigate analgesic use in a cohort of Danish youth elite athletes and compare weekly analgesic use over 36 weeks to student controls. We also investigated and compared reasons for analgesic use and types of analgesics used.